2004
DOI: 10.1073/pnas.0403048101
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating complex three-dimensional nanostructures with high-resolution conformable phase masks

Abstract: High-resolution, conformable phase masks provide a means to fabricate, in an experimentally simple manner, classes of 3D nanostructures that are technologically important but difficult to generate in other ways. In this approach, light passing through a phase mask that has features of relief comparable in dimension to the wavelength generates a 3D distribution of intensity that exposes a photopolymer film throughout its thickness. Developing this polymer yields a structure in the geometry of the intensity dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
314
0
5

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(321 citation statements)
references
References 33 publications
2
314
0
5
Order By: Relevance
“…A variant to holographic lithography in which the interference is created from a phase mask, as opposed to multiple beam interference, was demonstrated by Rogers and co-workers. [94] The phase mask is first defined in a 'master', fabricated through photolithography. This master is used to create a poly(dimethylsiloxane) (PDMS) flexible phase mask.…”
Section: Holographic Lithographymentioning
confidence: 99%
See 2 more Smart Citations
“…A variant to holographic lithography in which the interference is created from a phase mask, as opposed to multiple beam interference, was demonstrated by Rogers and co-workers. [94] The phase mask is first defined in a 'master', fabricated through photolithography. This master is used to create a poly(dimethylsiloxane) (PDMS) flexible phase mask.…”
Section: Holographic Lithographymentioning
confidence: 99%
“…[94] The phase mask is first defined in a 'master', fabricated through photolithography. This master is used to create a poly(dimethylsiloxane) (PDMS) flexible phase mask.…”
Section: Holographic Lithographymentioning
confidence: 99%
See 1 more Smart Citation
“…Odom and co-workers have shown that trenches generated by phase-shift photolithography can be used to direct the assembly of semiconductor quantum dots (Figure 122.9c) [130], and the growth of ZnO nanowires (NWs) into ordered arrays [131]. More recently, Rogers and co-workers have demonstrated the fabrication of 3D nanostructures, which derive from a rather complex intensity distribution within the bulk of a relatively thick photoresist layer (Figure 122.9d) [127,128].…”
Section: Patterning Based On Edge Effectsmentioning
confidence: 99%
“…This technique uses a topographic phase mask to mediate exposure of a thin film of photoresist to UV light [120][121][122][123][124][125][126][127][128][129].…”
Section: Patterning Based On Edge Effectsmentioning
confidence: 99%